K-ras and p53 mutations are an independent unfavourable prognostic indicator in patients with non-small-cell lung cancer. - Fukuyama, Y. (Nature Publishing Group, 1997)
We examined 159 consecutive cases of non-small-cell lung cancer (NSCLC) for a mutation at codon 12 of the K-ras gene and for a mutation of the p53 gene occurring in exons 5-8. Eleven (6.9%) had mutations of the K-ras (ras+) and 57 (35.8%) had mutations of the p53 (p53+). There were 95 cases (59.7%) with ras- p53-, seven cases (4.4%) with ras+/p53-, 53 cases (33.3%) with ras-/p53+ and four cases (2.5%) with ras+/p53+. The ras+ group had a worse prognosis than the ras group in all cases and in 107 early-stage cases (stage I-II, P<0.05). The p53+ group had a worse prognosis in 107 early-stage cases (P<0.01), but there was no statistically significant difference when 52 advanced-stage cases (stage III-IV) or all patients were considered. Both ras and p53 mutations were unfavourable prognostic factors in 94 cases with adenocarcinoma, but there was no statistical significance in 57 cases with squamous cell carcinoma. According to Cox's model, the pathological stage, ras mutation and p53 mutation were found to be independent prognostic factors. Our results suggest that ras and p53 mutations were independent unfavourable prognostic markers especially in the early stage of NSCLC or in adenocarcinoma.